Optimalisasi Peran Pemerintah Dalam Kebijakan Penanganan Limbah Medis - Annisa Hartami; Lego Karjoko; Fatma Ulfatun Najicha (PLEDOI (Jurnal Hukum dan Keadilan), 2023)
Law 32 of 2009 on Environmental Protection and Management is an example of the government's efforts to achieve a balance between economic growth and environmental preservation. In accordance with Human Rights (HAM) in realizing sustainable development and the existence of global environmental issues. This research method uses normative legal research methods that are prescriptive. Types and sources of law include primary and secondary legal materials. The technique of collecting legal materials used is the study of literature. Furthermore, the analysis technique used is the deductive method. The results of this study show that there is a need to optimize the role carried out by the government to deal with the growing medical waste.  In addition, health service facilities also carry out direct sorting to be more effective in handling the management of medical waste. This can be seen from the use of the Regulation of the Minister of Environment and Forestry Number p.56Menlhk-Setjen2015 as SPO in implementing medical waste management. These laws and regulations are able to provide legal expediency and certainty. Meanwhile, in terms of fairness, this is determined by how the implementation of these laws and regulations in the field.